Women’s Social Network and use of Family Planning Methods in Rural Uttar Pradesh, India - Pathak, Praveen Kumar (National Geographical Journal of India, 2022)
Although fertility has declined across several Indian states of late, with varying historical points of onset and pace of decline, women in Uttar Pradesh on average, still bear around four children in their reproductive lifetime due to the interplay of a complex set of socioeconomic, demographic and cultural factors. However, little attempt has been made in the past to examine the role of diffusion, aside from the standard set of socioeconomic factors in influencing fertility change in the Indian context. Using a unique ego-centric social network data, present study examine the informal interpersonal social network effect on the adoption of contraceptive and method choice among 567 currently married women in reproductive age groups in rural India. Bivariate and multivariate techniques were employed for data analysis. Findings suggest that social interaction appears to be a significant predictor of contraceptive method use among women after adjusting for pertinent socio-economic and demographic covariates.